2012
DOI: 10.4269/ajtmh.2012.11-0368
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of pfcrt and pfmdr1 Polymorphisms in P. falciparum Isolates from Nigeria and Brazil: The Potential Role of Antimalarial Drug Selection Pressure

Abstract: Abstract. The effect of antimalarial drug selection on pfcrt and pfmdr1 polymorphisms in Plasmodium falciparum isolates from two distinct geographical locations was determined in 70 and 18 P. falciparum isolates from Nigeria and Brazil, respectively, using nested polymerase chain reaction and direct DNA sequencing approaches. All isolates from Brazil and 72% from Nigeria harbored the mutant SVMNT and CVIET pfcrt haplotype, respectively. The pfcrt CVMNT haplotype was also observed in (7%) of the Nigerian sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
(34 reference statements)
4
17
2
Order By: Relevance
“…1). The fixation of the 76T allele is in agreement with other studies in Brazil [43, 55, 56], despite the withdrawal of CQ from national treatment guidelines in the mid-1980s [57]. The presence of the 76Y allele is in accordance with the description of isolates resistant to CQ in the same regions analysed here [43, 55].…”
Section: Resultssupporting
confidence: 91%
“…1). The fixation of the 76T allele is in agreement with other studies in Brazil [43, 55, 56], despite the withdrawal of CQ from national treatment guidelines in the mid-1980s [57]. The presence of the 76Y allele is in accordance with the description of isolates resistant to CQ in the same regions analysed here [43, 55].…”
Section: Resultssupporting
confidence: 91%
“…It is noteworthy that despite high grade chloroquine resistance and the association between transporter genes and resistance to chloroquine or amodiaquine in the area,20–24 artesunate-amodiaquine was still effective in the children < 5 years of age. The latter may be a result of the very limited use of amodiaquine monotherapy before the adoption of artesunate-amodiaquine as one of the first-line antimalarial drugs 10,25,26.…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by the antipyretic effect of the amodiaquine component of artesunate-amodiaquine 24,27. It is generally thought that the lumefantrine component of artemether-lumefantrine has little or no significant antipyretic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The different pfcrt mutant haplotypes have a consistent geographical distribution: the CQR haplotype CVIET is predominant in southeast Asia and Africa, whereas the AQ-resistant (AQR) haplotype SagtVMNT is predominant in Asia and South America, and StctVMNT, from South America, is very rare in Africa (16).The wild-type haplotype CVMNK is widespread (6,16,29,38). A recent study reported the presence of the StctVMNT haplotype of pfcrt in Angola, but this has not yet been verified by others (15,37).…”
mentioning
confidence: 99%
“…Mutations in this gene have some association with geographic areas. Considering codons 86, 184, 1034, 1042, and 1246, the pfmdr1 CQR haplotype YYSND is common in Asia and Africa, whereas NFCDY has occurred more frequently in CQ-resistant parasites in the Americas (16,24,29,38).…”
mentioning
confidence: 99%